2013
DOI: 10.1155/2013/982689
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculataExtract and Andrographolide Modulate the Hepatic Drug Metabolism System and Plasma Tolbutamide Concentrations in Rats

Abstract: Andrographolide is the most abundant terpenoid of A. paniculata which is used in the treatment of diabetes. In this study, we investigated the effects of A. paniculata extract (APE) and andrographolide on the expression of drug-metabolizing enzymes in rat liver and determined whether modulation of these enzymes changed the pharmacokinetics of tolbutamide. Rats were intragastrically dosed with 2 g/kg/day APE or 50 mg/kg/day andrographolide for 5 days before a dose of 20 mg/kg tolbutamide was given. APE and andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 58 publications
(56 reference statements)
2
25
0
1
Order By: Relevance
“…While elimination half-life and mean residence time of theophylline were shortened about 14 and 17 % in the andrographolide (77 mg/kg) pretreated group rats (Chao et al, 2010). Similarly Andrographis paniculata extract and andrographolide reduced the AUC 0-12h of tolbutamide by 37% and 18%, respectively (Chen et al, 2013). However, no significant effect of andrographolide on pharmacokinetics of warfarin (Hovhannisyan et al, 2006) and midazolam (Wongnawa et al, 2012) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…While elimination half-life and mean residence time of theophylline were shortened about 14 and 17 % in the andrographolide (77 mg/kg) pretreated group rats (Chao et al, 2010). Similarly Andrographis paniculata extract and andrographolide reduced the AUC 0-12h of tolbutamide by 37% and 18%, respectively (Chen et al, 2013). However, no significant effect of andrographolide on pharmacokinetics of warfarin (Hovhannisyan et al, 2006) and midazolam (Wongnawa et al, 2012) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…First, sets of data points were fitted to the following equation I to estimate the apparent Michaelis–Menten kinetic parameters: V = V max × S /( K m + S ), where V , V max , S , and K m are velocity of reaction, maximum reaction velocity, TB concentration, and Michaelis constant, respectively. On the other hand, it was reported that CYP2C6 and CYP2C11 are likely involved in TB 4‐hydroxylase activity in male rats (Chen et al, ; Dostalek et al, ; Wang et al, ). Therefore, assuming the involvement of these two enzymes in the metabolic reaction, the measurements were fitted to the following equation II: V = V max1 × S /( K m1 + S ) + V max2 × S /( K m2 + S ), where K m1 and K m2 correspond to the K m values of the low affinity and high affinity component, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…where V, V max , S, and K m are velocity of reaction, maximum reaction velocity, TB concentration, and Michaelis constant, respectively. On the other hand, it was reported that CYP2C6 and CYP2C11 are likely involved in TB 4-hydroxylase activity in male rats (Chen et al, 2013;Dostalek et al, 2007;Wang et al, 2010). Therefore, assuming the involvement of these two enzymes in the metabolic reaction, the measurements were fitted to the following equation II:…”
Section: Kinetic Analysis Of Hepatic Microsomal Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tolbutamide (TB) is a sulfonylurea derivative used as a hypoglycaemic agent in the management of type 2 diabetes mellitus. Previous kinetic studies suggested that tolbutamide is exclusively metabolized to 4‐hydroxytolbutamide (4‐OH‐TB) in rats as well as in humans and serves as a representative probe drug for CYP2C6/11 (Bogaards et al, ; Chen et al, ; Dostalek et al, ; Pekthong et al, ; Wang, Lee, Or, & Yeung, ). The aims of the present study were to examine whether the change in the expression level of hepatic CYP2C6/11 reflected the metabolic capacity of tolbutamide by conducting enzyme kinetic analysis of tolbutamide 4‐hydroxylation in hepatic microsomes of rats exposed to doxorubicin, and to investigate whether the in vitro enzyme activity is associated with the in vivo pharmacokinetics of total and unbound tolbutamide, while considering changes in the serum albumin concentration.…”
Section: Introductionmentioning
confidence: 99%